Traditions English National Ballet's Swan Lake - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2006)
English National Ballet's Swan Lake. When you take Swan Lake for granted it's easy to forget what a ridiculous story we're dealing with. PALABRAS CLAVE: Swan Lake, history, English National Ballet.